A HUNDRED YEARS' EXPERIENCE IN NATIONAL DERMATOVENEREOLOGY. STAGES OF DEVELOPMENT OF DERMATOVENEREOLOGICAL CARE FOR THE POPULATION (PART II) - Anna A. Kubanova; Andrey A. Martynov; Anna V. Vlasova (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
The stages of the formation of a model for the organization of dermatovenereological care to the population of the Russian Federation during the period from 1917 to 2017 were analyzed.